2021
DOI: 10.3390/bios11110454
|View full text |Cite
|
Sign up to set email alerts
|

Non-Interventional and High-Precision Temperature Measurement Biochips for Long-Term Monitoring the Temperature Fluctuations of Individual Cells

Abstract: Monitoring the thermal responses of individual cells to external stimuli is essential for studies of cell metabolism, organelle function, and drug screening. Fluorescent temperature probes are usually employed to measure the temperatures of individual cells; however, they have some unavoidable problems, such as, poor stability caused by their sensitivity to the chemical composition of the solution and the limitation in their measurement time due to the short fluorescence lifetime. Here, we demonstrate a stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In sharp contrast, if the same TFTC was made on a 400 nm thick, freestanding Si 3 N 4 thin-film, and the same measurement was repeated, the local temperature increment was 30 times higher than that on the Si wafer. Similarly, a local temperature increment peak was recorded at a focal point of an incident laser beam up to 2400 K, which was 100 times higher than that measured with the same sensors made on thick Si wafers [ 88 ]. The large difference measured in the sensitivity of the same TFTC sensors was attributed to the dissipation effect of heat.…”
Section: Main Issues Of the Micro-/nano-thin-film Thermocouple Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…In sharp contrast, if the same TFTC was made on a 400 nm thick, freestanding Si 3 N 4 thin-film, and the same measurement was repeated, the local temperature increment was 30 times higher than that on the Si wafer. Similarly, a local temperature increment peak was recorded at a focal point of an incident laser beam up to 2400 K, which was 100 times higher than that measured with the same sensors made on thick Si wafers [ 88 ]. The large difference measured in the sensitivity of the same TFTC sensors was attributed to the dissipation effect of heat.…”
Section: Main Issues Of the Micro-/nano-thin-film Thermocouple Approachmentioning
confidence: 99%
“…The development of a freestanding Si 3 N 4 thin-film window platform significantly improved the thermal sensitivity of the built-in micro-TC arrays for sensing individual cells. Recently, Han et al applied such a platform and observed local temperature increments of individual HeLa cells in the range of 10–50 mK [ 88 ].…”
Section: Main Issues Of the Micro-/nano-thin-film Thermocouple Approachmentioning
confidence: 99%
See 3 more Smart Citations